Tingkat Toleransi Pemuda Muslim di Kota Surabaya - Feryani Umi Rosidah (Religió: Jurnal Studi Agama-agama, 2019)
Surabaya is a multicultural city which consists of different communities, religions, and ethnics. However, the city has persisted to build harmonious relation between peoples. Based on Muslim-mayority population, the city attempts to cultivate inter-religious solidarity and understanding among the people. Known that political, economic, and religious matters could influence people’s behaviour, this research aims to see how the Muslim youth in the city understand and implement the social patterns of inter-religious relation. Using questionnaire method, the research found that 12.2% of the Muslim youth in Surabaya were very tolerant, 26.1% were tolerant, 28.9% were quite tolerant, 19.7% were intolerant, and 13.1% were very intolerant. This research also found that there are several factors influencing perceptions of Muslim youth in Surabaya for maintaining inter-religious tolerance, such as religion, politics, and social media.